MicroRNA-21: A Positive Regulator for Optimal Production of Type I and Type III Interferon by Plasmacytoid Dendritic Cells - Liu, Fang; Liu, Chunxi; Hu, Xiaoyu; Shang, Yingli; Wu, Li (Frontiers in Immunology, 2017)
Plasmacytoid dendritic cells (pDCs) are the major producers of type I and type III interferons (IFNs) that play essential roles in host antiviral immunity. MicroRNAs (miRs) are small, non-coding RNAs that can modulate many immune processes. Although the molecular regulation of type-I IFN production by pDCs has been studied extensively, the regulation of type-III IFN production has not been studied thoroughly, particularly at post-transcriptional level. In this study, we identified that microRNA-21 (miR-21) as an essential positive regulator for the production of both IFN-α and IFN-λ by pDCs and for promoting host defense against viral infection. MiR-21 was markedly upregulated in Toll-like receptor (TLR)-activated pDCs and was crucial for TLR7/9 ligand- or herpesvirus -induced production of IFN-α and IFN-λ by pDCs. MiR-21 deficient pDCs produced significantly lower levels of IFN-α and IFN-λ upon activation than that by wild-type pDCs. Impaired anti-viral immune responses were also observed in miR-21 deficient mice. Mechanistically, we revealed that the phosphatase and tensin homologue (PTEN) as the major target of miR-21 in pDCs and miR-21 deficiency resulted in increased expression of PTEN that suppressed TLR-mediated activation of PI3K-Akt-mTOR signaling in pDCs. Hence, our findings provide first evidence that miR-21 positively regulated both IFN-α and IFN-λ production and identified an important role for miR-21 in regulating the function of pDCs and in host antiviral immunity.